Pertanggungjawaban Hukum Pengelola Pondok Pesantren Atas Bangunan Pondok Pesantren Di Kawasan Rawan Bencana Iii - Angelica Michelle Stephanie Putri; Lanny Kusumawati; Erly Aristo (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Spatial planning is a system of spatial planning processes, space utilization and space utilization control. Spatial planning is carried out to be able to realize spatial order and provide welfare for the entire community. However, often there are many violations of the use of space committed by the community. O ne of them is the violation of space utilization by the Islamic Boarding School Manager for the existence of a boarding school building in the form of a special flat located in Purwobinangun Village, Pakem District, Sleman Regency without being equipped with a permit. The location is included in the Disaster Prons Area III, where this area is very dangerous because of its location very close to the volcano. Through the Jurifical Normative Research method by conducting a literature study on legal materials, the results obtained that the management can be charged with legal responbility in the form of imposing administrative sanctions relatrd to violations of space use because it was built in Disaster Prone Area III. Keywords: Violation of space utilization; Disaster Prone Area III; Legal Liability.